2009
DOI: 10.1017/s135246580999066x
|View full text |Cite
|
Sign up to set email alerts
|

Group Versus Individual Cognitive Treatment for Obsessive-Compulsive Disorder: Changes in Severity at Post-Treatment and One-Year Follow-up

Abstract: Group CBT is effective in decreasing OCD severity. The post-treatment changes were maintained one year later. Nevertheless, these changes were higher in the individual delivery of CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
1
12
0
3
Order By: Relevance
“…The worry levels in the ED groups are also elevated compared to individuals with Obsessive Compulsive Disorder (OCD; Cabedo et al, 2010) or psychosis (Startup, Freeman, & Garety, 2007). Over half of the AN participants and over one-third of the BN participants reported worry levels above the mean PSWQ score found in clinical GAD range (Startup & Erickson, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…The worry levels in the ED groups are also elevated compared to individuals with Obsessive Compulsive Disorder (OCD; Cabedo et al, 2010) or psychosis (Startup, Freeman, & Garety, 2007). Over half of the AN participants and over one-third of the BN participants reported worry levels above the mean PSWQ score found in clinical GAD range (Startup & Erickson, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…However, results of head-to-head trials are conflicting, with some RCTs finding no significant differences in efficacy between group and individual therapy [663,664], and others showing individual therapy to be superior [665-667]. Differences in results may be explained by the fact that in individual therapy the therapist may have the advantage of being more aware of the patient’s dysfunctional beliefs, however, the group therapy setting may offer the advantages of group encouragement, reciprocal support, imitation, and interpersonal learning which may result in an increased motivation and reduced discontinuation of treatment [62].…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
“…Six studies directly comparing group and individual ERP were included in the present analysis (Anderson & Rees, 2007;Cabedo et al, 2010;Fals-Stewart et al, 1993;Jaurrieta et al, 2008;Jonsson, Hougaard, & Bennedsen, 2011;O'Connor et al, 2005b). A previous metaanalysis (Jonsson & Hougaard, 2009) summarized the literature on group CBT for OCD and concluded that group and individual treatment gave equal outcome; however, also non-…”
Section: Treatment Aspectsmentioning
confidence: 99%